2020
DOI: 10.1016/j.cmet.2020.01.015
|View full text |Cite
|
Sign up to set email alerts
|

AMPK and TOR: The Yin and Yang of Cellular Nutrient Sensing and Growth Control

Abstract: This is an unusual plant-specific b subunit that contains the C-terminal domain but lacks a CBM (carbohydrate-binding module).b By sequence, this appears to be an ortholog of mammalian g subunits, but it does not appear to form functional heterotrimers (Zhao, 2019).This is an unusual plant-specific g subunit that contains a CBM (carbohydrate-binding module) fused to the four CBS motifs found in other AMPK-g subunits.dThis is probably a non-functional protein (Moreau et al., 2012).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
427
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 491 publications
(470 citation statements)
references
References 257 publications
(322 reference statements)
12
427
0
2
Order By: Relevance
“…AMPK, a master regulator of cell energy homeostasis, is activated when there is a lack of energy or nutrients [115]. AMPK downregulates mTORC1 in two ways.…”
Section: Ampk Activates Mtorc2mentioning
confidence: 99%
“…AMPK, a master regulator of cell energy homeostasis, is activated when there is a lack of energy or nutrients [115]. AMPK downregulates mTORC1 in two ways.…”
Section: Ampk Activates Mtorc2mentioning
confidence: 99%
“…This may indicate that pheromones in the CM activate more than one pathway and that they have to act in combination to elicit the full effect. Our findings that several energy-sensing pathways are involved in this process in A. freiburgensis, and that AMPK, insulin and TOR pathways are cross-regulated, are indicative of this hypothesis (González et al, 2020, Ruderman et al, 2010, Banerjee et al, 2016.…”
Section: Discussionmentioning
confidence: 56%
“…Key metabolic signaling pathways in macrophage activation include the mammalian target of rapamycin (mTOR), adenosine monophosphate (AMP) kinase (AMPK) and HIF-1a pathways. 64 There is increasing evidence that these pathways play important roles in regulating Leishmania granuloma formation as well as the polarization of macrophages within these tissues to form both permissive and nonpermissive niches within these tissues as outlined in the following sections.…”
Section: Role Of Macrophage Metabolic Signaling Pathways In Leishmanimentioning
confidence: 99%
“…Activation of murine macrophages with antiinflammatory cytokines, such as IL-4 or IL-13, promotes mTORC1 activation through the PI3K/protein kinase B (Akt) pathway, leading to increased protein synthesis and a switch to anabolic metabolism that is needed to sustain the energy-demanding functions of cell migration, cytokine production and tissue repair. 51,64 Infection of murine macrophages with L. donovani also leads to the activation of mTOR and polarization toward a permissive M2 phenotype, while inhibition of mTORC1 (via rapamycin treatment) limits parasite growth in ex vivo infected macrophages and granuloma development in mice. [67][68][69] Other studies have shown that mTORC1 activates a number of key downstream targets and transcription factors, including HIF-1a, peroxisome proliferator-activated receptor gamma coactivator 1-a, sterol regulatory element-binding protein-1 and PPAR-c, that lead to transcriptional upregulation of proteins involved in glucose uptake, glycolysis, mitochondrial biogenesis, oxidative phosphorylation, and fatty acid and cholesterol biosynthesis that individually or collectively may promote intracellular Leishmania growth.…”
Section: Mtor Signaling and Regulation Of Leishmania Growthmentioning
confidence: 99%